1995
DOI: 10.1063/1.113246
|View full text |Cite
|
Sign up to set email alerts
|

Gettering of copper to hydrogen-induced cavities in silicon

Abstract: Hydrogen implantation and subsequent thermal annealing is found to result in a well-defined band of cavities in Si. This band is an extremely efficient gettering layer for Cu which is also introduced into the near surface of Si by ion implantation. Profiling of implanted Cu indicates that ∼95% of an initial 3×1015 cm−2 Cu implant is redistributed following annealing at a temperature of 780 °C from a near-surface damaged layer to a narrow band of cavities of width ∼1000 Å at a depth of ∼1 μm. Furthermore, the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(49 citation statements)
references
References 5 publications
4
45
0
Order By: Relevance
“…Other work has shown that cavities can act as precipitation sites for Au [28], and might be implemented using this mechanism. We infer that if cavities are introduced, they might be able to getter some species by chemisorption while reducing the levels of stronger silicide-formers like Co and Fe by providing improved precipitation sites for them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other work has shown that cavities can act as precipitation sites for Au [28], and might be implemented using this mechanism. We infer that if cavities are introduced, they might be able to getter some species by chemisorption while reducing the levels of stronger silicide-formers like Co and Fe by providing improved precipitation sites for them.…”
Section: Discussionmentioning
confidence: 99%
“…In work done by Wong-Leung et al [28], the interaction of Au with cavities formed by implanting H has been studied in detail. In their experimental configuration, the Au migrates to the cavities and precipitates there, presumably via the eutectic reaction.…”
Section: I;mentioning
confidence: 99%
“…1. ͑a͒ SIMS Cu depth profile for the sample implanted at 40 keV, 8ϫ10 15 He ϩ /cm 2 , RT, channeling direction, contaminated by 1 ϫ10 12 Cu ϩ /cm 2 after 800°C/10 min RTA. The SIMS profile is combined with a XTEM bright field micrograph of the same sample.…”
Section: Random Implantationmentioning
confidence: 99%
“…3 The capture of metal impurities in MeV implanted Si has been detected by secondary ion mass spectrometry ͑SIMS͒ at the depth corresponding to the projected range, R p , of the implanted ions, where a buried layer of extended lattice defects can be observed by transmission electron microscopy ͑TEM͒. However, in addition to the gettering at R p , the trapping of metals at the R p /2 region has also been detected for MeV ion implanted Si in the 10 15 at/cm 2 fluence range, after thermal annealing in the 700-1000°C temperature interval. This phenomenon, called ''the R p /2 gettering effect'' was first observed by Tamura, Ando, and Ohya 4 by studying the gettering of O in czochralski ͑CZ͒ Si after MeV implantation of a variety of ions, such as C, F, Si, Ge, and As.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation